Odpowiedź:
a) [tex]3*27^{-\frac{2}{3} } *81^{\frac{3}{4} } =3*(3^{3})^{-\frac{2}{3} } *(3^{4} )^{\frac{3}{4} }=3*3^{-2} *3^{3} =3^{1-2+3} =9[/tex]
b) [tex]4^{3} *81^{\frac{1}{4} } *(\sqrt[5]{32} )^{-1} =4^{3}*(3^{4} )^{\frac{1}{4} } *(\sqrt[5]{2^{5} }) ^{-1} =4^{3}*3*\frac{1}{2} =64*\frac{1}{2} *3=96[/tex]
c) [tex]log_{8} 2=c[/tex]
[tex]8^{c} =2[/tex]
[tex]8^{c} =8^{\frac{1}{3} }[/tex]
[tex]c=\frac{1}{3}[/tex]
[tex]log_{8} 2=\frac{1}{3}[/tex]
d) [tex]log3 +log2-log6 =log(3*2)-log6=log6-log6=log(\frac{6}{6} )=log1=0[/tex]